On the taxonomy of genus Compsoctena Zeller, 1852 (Lepidoptera: Eriocottidae) from India and Bangladesh, with descriptions of three new species - Rayhan, Md Jahir; Ahmad, Jalil; Joshi, Rahul; Singh, Navneet; Sobczyk, Thomas (Zootaxa, 2026)
This work deals with the taxonomy of genus Compsoctena from India and Bangladesh, based on fresh material and historical collections housed in the Lepidoptera section of the Zoological Survey of India, Kolkata. Three new species, Compsoctena kushabhadrae sp. nov., C. kamaraji sp. nov. (India), and C. faridahsani sp. nov. (Bangladesh) are described as new. The following new combinations are proposed based on primary types housed in the Natural History Museum, London: Compsoctena accurata (Meyrick, 1922), comb. nov.; Compsoctena autochthonia (Meyrick, 1931) comb. nov.; Compsoctena certatrix (Meyrick, 1916), comb. nov.; Compsoctena coagulata (Meyrick, 1919), comb. nov.; Compsoctena colonica (Meyrick, 1916) comb. nov.; Compsoctena cremata (Meyrick, 1916), comb. nov.; Compsoctena deposita (Meyrick, 1919) comb. nov.; Compsoctena devincta (Meyrick, 1916) comb. nov.; Compsoctena expedita (Meyrick, 1907) comb. nov.; Compsoctena exsecrata (Meyrick, 1937) comb. nov.; Compsoctena gregaria (Meyrick, 1916) comb. nov.; Compsoctena infensa (Meyrick, 1916) comb. nov.; Compsoctena isopeda (Meyrick, 1907) comb. nov.; Compsoctena jactata (Meyrick, 1937) comb. nov.; Compsoctena lignosa (Meyrick, 1917) comb. nov.; Compsoctena meliphaea (Meyrick, 1916) comb. nov.; Compsoctena multiplex (Meyrick, 1917) comb. nov.; Compsoctena nota (Meyrick, 1919) comb. nov.; Compsoctena obtrectans (Meyrick, 1930) comb. nov.; Compsoctena paraclasta (Meyrick, 1922) comb. nov.; Compsoctena phaeogenes (Meyrick, 1919) comb. nov.; Compsoctena pericrossa (Meyrick, 1907) comb. nov.; Compsoctena praecepta (Meyrick, 1919), comb. nov.; Compsoctena ptyalistis (Meyrick, 1937) comb. nov.; Compsoctena semota (Meyrick, 1938) comb. nov.; Compsoctena subacta (Meyrick, 1919) comb. nov.; Compsoctena tylota (Meyrick, 1916) comb. nov., and Compsoctena vorticosa (Meyrick, 1930) comb. nov. Although all these species were originally described under the genus Melasina, their current taxonomic placement is reviewed and discussed in detail. Additionally, three new country records, Compsoctena thwaitesii (Walsingham, 1887), and C. anasactis (Meyrick, 1907) from India, and Compsoctena pulla Sobczyk & Breithaupt, 2023 from Bangladesh are provided. An updated checklist of Compsoctena from India and Bangladesh is given arranging the species into ten species groups based on male wing maculation.